HSV: The scout and assault for digestive system tumors - Li, Sheng; Li, Qingbo; Ren, Yi; Yi, Jia; Guo, Jinhe; Kong, Xianbin (Frontiers in Molecular Biosciences, 2023)
More than 25% of all malignant tumors are digestive system tumors (DSTs), which mostly include esophageal cancer, gastric cancer, pancreatic cancer, liver cancer, gallbladder cancer and cholangiocarcinoma, and colorectal cancer. DSTs have emerged as one of the prominent reasons of morbidity and death in many nations and areas around the world, posing a serious threat to human life and health. General treatments such as radiotherapy, chemotherapy, and surgical resection can poorly cure the patients and have a bad prognosis. A type of immunotherapy known as oncolytic virus therapy, have recently shown extraordinary anti-tumor effectiveness. One of the viruses that has been the subject of the greatest research in this field, the herpes simplex virus (HSV), has shown excellent potential in DSTs. With a discussion of HSV-1 based on recent studies, we outline the therapeutic effects of HSV on a number of DSTs in this review. Additionally, the critical function of HSV in the detection of cancers is discussed, and some HSV future possibilities are shown.